2016
DOI: 10.1016/j.ijrobp.2016.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Imaging and Cognition in Juvenile Rats After Whole-Brain Irradiation

Abstract: Purpose In pediatric cancer survivors treated with whole-brain irradiation (WBI), long-term cognitive deficits and morbidity develop that are poorly understood and for which there is no treatment. We describe similar cognitive defects in juvenile WBI rats and correlate them with alterations in diffusion tensor imaging and magnetic resonance spectroscopy (MRS) during brain development. Methods and Materials Juvenile Fischer rats received clinically relevant fractionated doses of WBI or a high-dose exposure. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…Interestingly in this preclinical model, the deleterious effects on FA are more prominent if the dose is delivered to the whole body and not restricted only to the head (Gupta et al, 2013;Trivedi et al, 2012), indicating an important systemic influence on brain response. With more specific relevance to childhood cancer treatment, similar decreases in FA have also been reported in juvenile rats after cranial radiation (Brown et al, 2016;Rodgers et al, 2016), with decreases in FA observed in the corpus callosum and fimbria. These DTI changes were accompanied by a significant decrease in total brain volume in adulthood (Rodgers et al, 2016).…”
Section: Neuroimaging For Translationsupporting
confidence: 70%
“…Interestingly in this preclinical model, the deleterious effects on FA are more prominent if the dose is delivered to the whole body and not restricted only to the head (Gupta et al, 2013;Trivedi et al, 2012), indicating an important systemic influence on brain response. With more specific relevance to childhood cancer treatment, similar decreases in FA have also been reported in juvenile rats after cranial radiation (Brown et al, 2016;Rodgers et al, 2016), with decreases in FA observed in the corpus callosum and fimbria. These DTI changes were accompanied by a significant decrease in total brain volume in adulthood (Rodgers et al, 2016).…”
Section: Neuroimaging For Translationsupporting
confidence: 70%
“…In addition to the prefrontal and entorhinal cortex, the corpus callosum has also been reported to be associated with mild cognitive impairment (Blasi et al, 2014 ; Brown et al, 2016 ). Therefore, we performed immunofluorescence staining of MBP (a marker of myelin integrity) and SMI-32 (a marker of abnormally dephosphorylated neurofilament protein) to further evaluate pathological changes in the corpus callosum, as well as LFB staining (a method used to stain myelin and phospholipids) in the corpus callosum.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, there are few studies reported the effect of exercise training on the nonspatial learning and memory of rodents after stroke. It has been proposed that the prefrontal lobe, entorhinal cortex and corpus callosum are involved in nonspatial learning and memory processes (Yee and Rawlins, 1998 ; Granon and Poucet, 2000 ; Blasi et al, 2014 ; Brown et al, 2016 ). However, the exact brain regions and mechanisms by which PE impacts stroke-induced nonspatial learning and memory deficit are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…One can choose to perform the novel object recognition (NOR) task and the novel location recognition (NLR) tasks using a short retention interval (minutes) as a measurement of hippocampus-independent, prefrontal cortex-dependent memory, or long retention interval (hours) for hippocampal-dependent learning. While the short-term interval version resulted in defects after irradiation 23,24,41,[47][48][49][50][51][52] , the hippocampal-dependent version of the NOR was not always affected after irradiation [53][54][55] . Interestingly, performance on the NOR was found to be dependent on dose, dosing-regimen and timing 53,54,56 .…”
Section: Discussionmentioning
confidence: 96%
“…While the short-term interval version resulted in defects after irradiation 23,24,41,4752 , the hippocampal-dependent version of the NOR was not always affected after irradiation 5355 . Interestingly, performance on the NOR was found to be dependent on dose, dosing-regimen and timing 53,54,56 . In addition, male C57BL/6 mice only perform well at the NOR at 3 months, but not at older age 57 and short timeframes are required to capture NOR 57 .…”
Section: Discussionmentioning
confidence: 99%